GLUCOCORTICOID WITHDRAWAL SYNDROME MASQUERADES AS UNEXPLAINED PERSISTENT FEVER - Wong, Wei Ton; Hadie, Dian Fitria binti Abdul (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND With the availability of over-the-counter medicine, individuals have turned to the convenient means of receiving their supply of medicine instead of thorough physician consultation. Steroids are one of the over-the-counter medicines that are often used inappropriately to manage chronic pain. When steroids are used at supraphysiological doses for a prolonged period, it suppresses the hypothalamic-pituitary-adrenal axis. In this review, we present a case of unexplained persistent fever which responds miraculously to steroids. CASE A 77-year-old male with underlying type 2 diabetes mellitus, hypertension, dyslipidemia, chronic obstructive pulmonary disease and degenerative spine disease presented with a 3-day history of diarrhea, abdominal pain, poor appetite and altered mental status. Skin examination shows skin thinning and multiple bruises. X-rays, imaging and CT scan were unremarkable. One week after hospitalization, he developed a fever, which was attributed to thrombophlebitis of the left forearm. Multiple antibiotics were infused: IV Ceftriaxone, IV Piperacillin / Tazobactam, IV Meropenem, IV Vancomycin and T Doxycycline. There is no positive culture, aside from the urine culture growing Enterococcus faecalis, susceptible to Vancomycin. Still, the fever persisted until the trial of IV hydrocortisone 100 mg TDS for the possibility of fever caused by glucocorticoid withdrawal syndrome. After 1 full day of IV hydrocortisone, the fever resolved. CONCLUSION Unexplained fever remains a diagnostic and therapeutic challenge. A full workup of fever does not reveal the source of infection. Despite multiple antibiotics, fever does not settle until introduction of glucocorticoid. With suggestive history of chronic pain, skin thinning and remarkable response to glucocorticoid, glucocorticoid withdrawal syndrome is one the causes of unexplained persistent fever that we should all not miss.